1998
DOI: 10.1152/ajplung.1998.274.3.l360
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive nitric oxide production by rat alveolar macrophages

Abstract: Results from previous studies suggest that alveolar macrophages must be exposed to inflammatory stimuli to produce nitric oxide (⋅ NO). In this study, we report that naive unstimulated rat alveolar macrophages do produce ⋅ NO and attempt to characterize this process. Western blot analysis demonstrates that the enzyme responsible is an endothelial nitric oxide synthase (eNOS). No brain or inducible NOS can be detected. The rate of ⋅ NO production is ∼0.07 nmol ⋅ 106cells−1 ⋅ h−1, an amount that is less than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
3
27
0
1
Order By: Relevance
“…In animal systems, it has been reported that extracellular calcium induces NO production (Miles et al, 1998). In this study, we have checked NO levels after treatment with extracellular calcium, and the results indicated that NO levels in the guard cells of the wild type increased when treated with extracellular calcium (Fig.…”
Section: No Plays An Important Role In Extcam Guard Cell Signalingmentioning
confidence: 60%
“…In animal systems, it has been reported that extracellular calcium induces NO production (Miles et al, 1998). In this study, we have checked NO levels after treatment with extracellular calcium, and the results indicated that NO levels in the guard cells of the wild type increased when treated with extracellular calcium (Fig.…”
Section: No Plays An Important Role In Extcam Guard Cell Signalingmentioning
confidence: 60%
“…1A). Expression of constitutive NOSs present in addition to iNOS and generating NO in the absence of inflammatory stimuli has been demonstrated in various cell types including rodent macrophages (22)(23)(24). However, in dendritic cells from both wild-type and iNOS Ϫ/Ϫ mice, endothelial nitric oxide synthase as well as neuronal nitric oxide synthase mRNA expression were close to the detection limit of ϳ5 ϫ 10 Ϫ9 mRNA copies per 18 S rRNA (data not shown).…”
Section: Effect Of Pteridines and L-nil On Dendritic Cellsmentioning
confidence: 81%
“…Thus, given our results with L-NAME, it seems that histamine stimulates NO release through a cNOS pathway. Although AMs are well known to produce NO through iNOS, unstimulated AMs can also produce NO via cNOS (45). This may explain why histamine alone stimulated the release of NO, but did not potentiate its release when histamine-pretreated AMs were stimulated with LPS, which increases iNOS.…”
Section: Discussionmentioning
confidence: 99%